THE APPLICATION OF NESTED DISSECTION TO THE SOLUTION OF A 2.5D ELECTROMAGNETIC PROBLEM - Smith, G. H. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
We use the method of nested dissection to solve a 2.5D finite difference electromagnetic problem. This method is considered in some detail, and we have found that the expected theoretical run time savings over more common methods are realised in practice. The program has been used to model EM propagation in coal seams with a view to detecting seam disruptions, which can cause a loss of production in longwall mining operations. Various experimental results and a field survey are discussed and we are able to use these results to construct a physically reasonable model which explains the field data. Some further realistics geological structures are modelled and a comparison between our modelling program and several independent methods shows satisfactory agreement.